Advisory Material for the IAEA Regulations for the Safe Transport of Radioactive Material (2018 Edition) : specific safety guide. (Safety standards series ;, 2022)
"This Safety Guide provides recommendations and guidance on achieving and demonstrating compliance with IAEA Safety Standards Series No. SSR-6 (Rev. 1), Regulations for the Safe Transport of Radioactive Material (2018 Edition), which establishes the requirements to be applied to the national and international transport of radioactive material. Transport is deemed to comprise all operations and conditions associated with and involved in the movement of radioactive material, including the design, fabrication and maintenance of packaging, and the preparation, consigning, handling, carriage, storage in transit, shipment after storage and receipt at the final destination of packages. The Advisory Material is not a stand-alone text. It is to be used concurrently as a companion to the IAEA Safety Standards Series No. SSR-6 (Rev. 1) and each paragraph of this guide is numbered correspondingly to the paragraph of the Regulations to which it most directly relates."--Publisher's description.